Effects of Methyl and Isopropyl N‐methylanthranilates from Choisya ternata Kunth (Rutaceae) on Experimental Anxiety and Depression in Mice. (7th November 2012) - Radulović, Niko S.; Miltojević, Ana B.; Randjelović, Pavle J.; Stojanović, Nikola M.; Boylan, Fabio
Abstract : Choisya ternata Kunth (Rutaceae) is a plant species used in Mexican folk medicine for its antispasmodic and simulative properties. Recently, we identified a new alkaloid, isopropyl N ‐methylanthranilate, and a related one, methyl N ‐methylanthranilate, from the essential oil of this species and have proven them to possess antinociceptive activity even at 0.3 mg/kg. In the present study, anxiolytic and antidepressant effects of the two compounds have been studied in open field, horizontal wire, light/dark, forced swimming and tail suspension tests, as well as the effect on the onset and duration of diazepam‐induced sleep in BALB/c mice. The volatile alkaloids (50–200 mg/kg, administered intraperitoneally), without having a muscle relaxant effect, caused a significant increase in the time the animals spent in an unsecured and putatively dangerous area when compared with the control group but had no effect on the number of crossings between the light/dark compartments. In addition to this anxiolytic activity, a significantly antidepressant‐like effect was apparent at all tested doses, which was not due to an increase in locomotive activity. The anthranilates administered on their own did not induce sleep in mice but significantly prolonged the diazepam‐induced sleep, in a dose‐dependent way, suggesting an interaction with the gamma‐aminobutyric acid receptor complex. Copyright © 2012 John Wiley & Sons, Ltd.